Research on Complex Data Management and Analysis at UFSC - Mello, Ronaldo dos Santos; Fileto, Renato; Dorneles, Carina F.; Bogorny, Vania (Journal of Information and Data Management, 2011)
Since the end of the 20th century data have been gathered in an unprecedented and growing scale, by using a variety of devices and information systems, ranging from sensors to the social Web. The resulting heterogeneous collections of unconventional data, particularly complex data (XML, Web data, maps, time series, etc.), cannot be constrained just to relational tuples, and require new methods for data handling and information extraction. This article introduces the research efforts on unconventional complex data management and analysis being developed by the database group of the Universidade Federal de Santa Catarina. First, it gives a brief description of the group. Second, it presents some of the main research efforts and directions of the group, in the topics of data modeling, data matching, information retrieval, and spatial and spatio-temporal data analysis. Third, it discusses the impact of these research efforts, as well as the interactions of the group with other institutions. Finally, it points out some research perspectives and collaborations with academia and the industry.